The state is in the trenches of existential destiny - Harutyunyan, Edvard (Bulletin of Yerevan University E: Philosophy, Psychology, 2021)
Considering the national culture of organizing and regulating life as a social embodiment of the soul of the people, in the historical context of the formation of the narratives of the Motherland and the State, a number of unsolved problems of modernizing national identity, as well as the correlation and reconciliation of the existential and civilizational destinies of the Armenian people, which in borderline situations give rise to problems and challenges, are analyzed. not corresponding to the internal capabilities of the country.